Penile Fractures: the Successful Outcome of Immediate Surgical Intervention - Nadir Shah, Imran Uddin Khan, Rashid Aslam, Ayesha Latif (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the results of early surgical repair in patients who initially report with a penis fracture. Study design: Retrospective Study Place of study & duration: General Surgery Department Hayatabad Medical Complex Peshawar from January 2020 to December 2021. Methodology: 42 patients with penile fractures who presented to the emergency room of the Hayatabad Medical Complex in Peshawar were included in this retrospective analysis. A clinical diagnosis was made. There was no radiological analysis done. All patients had primary suturing for the tunica tear and underwent postoperative monitoring for 4 months. Results: All patients underwent surgery within 24 hours of the injury. The most common cause of injury was sexual intercourse 35(83.3%) followed by 3(7.1%) masturbation, 2(4.8%) rolling over in bed and 2(4.8%) during “routine stretching.” Every patient consistently reported hearing a cracking sound along with a severe pain, erection loss, deformity, discolouration, and edoema. Only 3 patients had blood at the external meatus. No extravasation was detected by ascending urethrography. There were 20(47.6%) proximal injuries, 16(38%) midshaft injuries and 6(14.3%) distal injuries. Conclusion: An acceptable complication rate and satisfactory postoperative results are associated with early surgical intervention for penile fracture. Early diagnosis and surgical intervention are essential for a positive result and minimal complications. Keywords: Penile fracture, Tunica albugenia, corpus cavernosum